Cave millipedes of the United States. XIII. A new, troglobiotic species of Austrotyla from Colorado (Diplopoda, Chordeumatida, Conotylidae) - Shear, William A.; Steinmann, David B. (Zootaxa, 2013)
Austrotyla stephensoni n. sp., from Colorado, is described as the first troglobiotic species of its genus, and compared to sympatric Austrotyla coloradensis (Chamberlin 1910). A key to all Austrotyla species is provided.